2007
DOI: 10.1038/nature06289
|View full text |Cite
|
Sign up to set email alerts
|

A synaptic memory trace for cortical receptive field plasticity

Abstract: A synaptic memory trace for cortical receptive field plasticity. Neuromodulation is required for cortical plasticity, but it is uncertain how subcortical neuromodulatory systems, such as the cholinergic nucleus basalis ( A major subcortical nucleus critical for receptive field plasticity is NB, the main source of cortical acetylcholine (ACh) 4,9,[14][15][16][17][19][20][21] . How are neuromodulators such as ACh involved in plasticity, and what circuit elements do they act upon? One possibility is that neuromod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
593
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(627 citation statements)
references
References 32 publications
26
593
3
5
Order By: Relevance
“…[Although Beierlein et al (35) have shown slow oscillations generated by LTS cells coupled by gap junctions in thalmo-cortical slices, such synchronization would not necessarily preclude their providing the bath of inhibition that we postulate; this bath does not have to be tonic.] Froemke et al (36) have shown that activation of nucleus basalis, the main source of acetylcholine in the cortex, leads to a rapid reduction of synaptic inhibition in rat primary auditory cortex; our assumption is in line with this result.…”
Section: Discussionsupporting
confidence: 88%
“…[Although Beierlein et al (35) have shown slow oscillations generated by LTS cells coupled by gap junctions in thalmo-cortical slices, such synchronization would not necessarily preclude their providing the bath of inhibition that we postulate; this bath does not have to be tonic.] Froemke et al (36) have shown that activation of nucleus basalis, the main source of acetylcholine in the cortex, leads to a rapid reduction of synaptic inhibition in rat primary auditory cortex; our assumption is in line with this result.…”
Section: Discussionsupporting
confidence: 88%
“…However, in a recent study of plasticity mediated by nucleus basalis stimulation in the adult auditory cortex, excitation and inhibition underwent a similar transient mismatch of response properties, although the mismatch lasted hours instead of days (34). The similarity of our results in developing visual cortex to those in adult auditory cortex suggests that the transient imbalance of local excitatory and inhibitory cells during change may be a general property of cortical circuit reorganization.…”
Section: Discussionsupporting
confidence: 72%
“…Control (unmanipulated) animals were imaged at ages that spanned the critical period (postnatal days [25][26][27][28][29][30][31][32][33][34][35]. Imaging sessions began with intrinsic signal mapping of the binocular zone to locate the binocular portion of the primary visual cortex.…”
Section: Methodsmentioning
confidence: 99%
“…This parallel instructive signaling at the level of neural circuits and intracellular signaling pathways could enhance the flexibility and computational power of the learning system. This type of teaching signal mechanism may confer an evolutionarily adaptive benefit on the organism and be conserved across neural circuits and species (3,11,16,70). It will be important to determine how these signals are computed in these parallel neural pathways to the LA and how they interact in LA neuronal intracellular signaling networks.…”
Section: Discussionmentioning
confidence: 99%